Efektifitas Penerapan Sistem Electronic Traffic Law Enforcement Di Kota Palu - Syamsu, Mohammad Sahbani; Djaelangkara, Rizali; Firmansyah, Andi Maman (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to find out how effective the implementation of the Electronic Traffic Law Enforcement System in Palu City. The basis for this application uses a qualitative research basis with a descriptive approach, while data collection techniques are carried out by observation, interviews, and documentation. The determination of informants in this study uses purposive by assigning 4 (people) informants. The data analysis in this study is data collection, data condensation, data display, and conclusion drawn. As for the theory used in this study, namely the theory by Duncan, there are 3 aspects that need to be considered, namely 1) Goal achievement, 2) Integration, 3) Adaptation. Based on the results of the research obtained, it can be concluded that the factor that causes the implementation of electronic tickets in the city of Palu is still a lack of public awareness of the existence of electronic tickets because there are still many traffic violations in locations where ETLE cameras are installed, in addition to that there is still a lack of budget in its implementation so that there are still many locations prone to traffic violations that have not been installed ETLE cameras so that there are still There are many traffic violations in Palu City.